POLÍTICAS E PRÁTICAS DE FORMAÇÃO CONTINUADA DE PROFESSORES NO ESPÍRITO SANTO MEDIADAS PELOS PLANOS DECENAIS DE EDUCAÇÃO. - Oliveira, Dalva Ricas de (2022)
This research investigates the policies and practices of continuing education of teachers in Espírito Santo (ES) mediated by the National, State and Municipal Education Plans (PNE, PEE-ES and PMEs), within the scope of the Municipal Education Departments (Semes) of ES. It aims to identify and understand the elements that influence the training managers of the Semes of the State of ES, to the translation of the continuing education policies for teachers established in the ten-year education plans. It is based on the theoretical production of Michel de Certeau, Stephen Ball and collaborators and António Nóvoa as main theoretical contributions. It is an exploratory, qualitative-quantitative research, which includes three fronts: bibliographic, documentary and field research. The methodological procedures include: conducting studies to review academic production - theses and dissertations - selected in the Catalog of Theses and Dissertations of the Coordination for the Improvement of Higher Education Personnel (Capes), on educational policies for continuing education of teachers centered on the PNE, PEE-ES and SMEs, produced between 2014 and 2020; document analysis of laws approving ten-year education plans, decrees and national resolutions; conducting a survey in the Semes of 62 municipalities in Espírito Santo; and, from semi-structured interviews with the subjects of the subsample – the managers of the continuing education of 10 Semes do ES participating in the research. The results indicate that Semes do ES are contexts of policy practice, insofar as continuing education managers, albeit in a microbial way, play an active role in these spaces, transforming continuing education policies for teachers into practices more in line with the local demands and challenges. They also show that the active role of these subjects in the process of translating the continuing education policies established in the ten-year education plans is influenced by diverse elements such as initial and continuing education, experience, management of Semes, external partnerships and the local politics that cause estrangement and promote significant transformations in the actions of these actors on the originally planned policies.